2017
DOI: 10.2147/clep.s149574
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the LACE index to predict 30-day hospital readmissions in patients with chronic obstructive pulmonary disease

Abstract: Background and objectivePatients hospitalized for acute exacerbation of chronic obstructive pulmonary disease (COPD) have a high 30-day hospital readmission rate, which has a large impact on the health care system and patients’ quality of life. The use of a prediction model to quantify a patient’s risk of readmission may assist in directing interventions to patients who will benefit most. The objective of this study was to calculate the rate of 30-day readmissions and evaluate the accuracy of the LACE index (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 32 publications
6
53
1
1
Order By: Relevance
“…Patients with the highest LACE+ scores were 2.18 to 2.42 times as likely to be seen in the ED, 1.93 to 5.16 times more likely to be readmitted, and 1.75 to 2.30 times more likely to have a reoperation than patients with lower LACE+ scores. These results support the conclusions of prior studies supporting LACE+ prediction of short‐term outcomes after hospital discharge 18,20,21,23 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Patients with the highest LACE+ scores were 2.18 to 2.42 times as likely to be seen in the ED, 1.93 to 5.16 times more likely to be readmitted, and 1.75 to 2.30 times more likely to have a reoperation than patients with lower LACE+ scores. These results support the conclusions of prior studies supporting LACE+ prediction of short‐term outcomes after hospital discharge 18,20,21,23 …”
Section: Discussionsupporting
confidence: 90%
“…The developers of LACE subsequently modified it to create the LACE+ index using multivariable logistic regressions to identify suitable predictors that were incorporated into the new index as per Sullivan et al 16 The final statistical evaluation of the LACE+ index's effectiveness using the Hosmer‐Lemeshow goodness‐of‐fit test was found to have good to excellent discriminative ability and improved predictive capacity relative to the original algorithm 17 . The LACE and LACE+ indices have each been tested in a number of medical and surgical populations with varying success 18‐25 . Although previous work has demonstrated that LACE is able to predict readmission risk after orthopedic surgery, 26 LACE+ has never been tested in an orthopedic surgery population.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a review concluded that age was consistently associated with short‐term mortality in hospitalized COPD adults . Age is a physiological parameter used in many disease indices and clinical scales such as the APACHE and LACE score. Multimorbidity, progressive muscle atrophy and lung function loss, declining biological cell and system dysfunction are among the factors underlying the increased mortality risk with aging .…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a significant association between high blood eosinophils and all-cause readmission at 30 and 60 days may be because only 30–60% of all-cause readmissions are attributable to COPD, with other causes being due to comorbidities or socioeconomic factors that may not be associated with blood eosinophils. 27 29 …”
Section: Discussionmentioning
confidence: 99%